Penerapan Media Kotak Simpati dalam Meningkatkan Keterampilan Menulis Ungkapan Kepedulian Murid Kelas VII SMP Negeri Surabaya - Alifa Septiani Putri; Fafi Inayatillah (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
This study aims to describe the process of implementing the Sympathy Mailbox media in writing expressions of concern by knowing the improvement in student learning outcomes and their responses. This study uses experimental research with a quantitative descriptive approach and a pretest-posttest control group design. The subjects involved were 64 seventh-grade students of SMP Negeri 47 Surabaya. Data collection included observation, tests, and questionnaires with data analyzed in the form of percentages, means, and t-tests. The results obtained showed that the learning process ran very well starting from the preparation stage in the form of providing two sympathy boxes, the implementation stage and the evaluation stage through the final test and response questionnaire. This can be proven by the percentage of student activity of 93.75% and educators 90%. The average student learning score increased in the pre-test from 75.12 to 84.37 with a gain value of 9.31. The t-test produced a t-count value of 9.23 which was higher than the t-table, this proved that there was a significant influence of the sympathy mailbox media on the ability to write expressions of concern. The students' response to the learning was very positive, so it can be concluded that the process of implementing the sympathy box media in learning was successful.